Histopathological changes and lipid metabolism in the liver of Bufo gargarizans tadpoles exposed to Triclosan. (September 2017) - Chai, Lihong; Chen, Aixia; Luo, Pingping; Zhao, Hongfeng; Wang, Hongyuan
Abstract: In the current study, the adverse effects of TCS on liver health of B. gargarizans tadpoles were assessed. B. gargarizans larvae were exposed to TCS at 0, 10, 30, 60, and 150 μg L −1 from Gosner stage 3 until metamorphic climax. The hepatosomatic index (HSI), hepatic histological and ultrastructural features, and transcript levels of genes associated with detoxification and oxidative stress as well as lipid metabolism in the livers were determined. Exposure to 150 μg L −1 TCS resulted in increased HSI of tadpoles at metamorphic climax. Histological changes characterized by an increase in the number of melanomacrophage, nucleus pyknosis, and deposition of collagen fibers were observed in liver at 60 and 150 μg L −1 TCS. Moreover, marked ultrastructural alterations including high electron dense in mitochondrial matrix and lipid accumulation were also observed. In addition, abundances of transcripts of Cu/Zn superoxide dismutase ( SOD ), phospholipid hydroperoxide glutathione peroxidase ( PHGPx ), and heat shock protein 90 ( HSP 90 ) were decreased in larvae exposed to 60 and 150 μg L −1 TCS, while transcript level of HSP 90 was increased at 30 μg L −1 TCS. Also, abundances of transcripts of acetyl-CoA carboxylase ( ACC ), carnitine palmitoyltransferase 2 ( CPT2 ), peroxisome proliferator-activated receptor alpha ( PPARa ), fatty acid elongase 1 ( FAE ), sterol carrier protein 2 ( SCP ) were significantly lesser in larvae exposed to 60 and 150 μg L −1 TCS. Overall, TCS at high levels induced histopathological changes in the liver of B. gargarizans tadpoles. This might have been due to the alteration of oxidative stress–related genes and lipid metabolism-related genes expression levels. Highlights: TCS induced marked histological changes in the liver of tadpoles. Hepatic ultrastructural alterations were also observed in exposed animals. Transcript levels of key genes involved in lipid metabolism were altered by TCS exposure. TCS induced alterations of mRNA levels of detoxification and oxidative stress genes.